2015
DOI: 10.3844/ajbbsp.2015.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Skin Secretion of Bleeding Toad <i>Leptophryne Cruentata</i> and Javan Tree Frog <i>Rhacophorus Margaritifer</i>

Abstract: Amphibian skin has been the source of a wide variety of biologically active compounds. This study was aimed to determine antifungal activity of skin secretion of two species of anurans endemic in Indonesia, the bleeding toad Leptophryne cruentata and the javan tree frog Rhacophorus margaritifer. We collected 7 adults of L. cruentata and 10 adults of R. margaritifer from the wild in Mount Gede Pangrango National Park, West Java. The toads and frogs were induced to release skin secretion using a nonlethal induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The skin secretions of specimen RJ9 contained about 2.4% of pentadecanone (Artika et al, 2015). Volatile components of the plant Minuartia meyeri of northeastern Turkey, which contains pentadecanone as one of the major components, was active in inhibiting growth of Yersinia pseudotuberculosis, Enterococcus faecalis and S. aureus (Yayli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The skin secretions of specimen RJ9 contained about 2.4% of pentadecanone (Artika et al, 2015). Volatile components of the plant Minuartia meyeri of northeastern Turkey, which contains pentadecanone as one of the major components, was active in inhibiting growth of Yersinia pseudotuberculosis, Enterococcus faecalis and S. aureus (Yayli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical components of the toad and frog skin secretions used in this study have been reported (Artika et al, 2015). Compounds with potential antibacterial activity include: fatty acids, triacontane, nonadecane, heptadecane, pregnane, pentadecanone, nonacosane, palustrol and myrtenol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin secretions of Leptophryne cruentata show antifungal activity against Trichophyton mentagrophytes ; forty microliters caused an inhibition halo of 14.5 ± 2.9 mm diameter [ 51 ]. Furthermore, the skin secretions of Rhinella icterica showed antifungal activity against Candida krusei [ 28 ].…”
Section: Antimicrobial Activities Of Compounds From Toads’ Cutaneous ...mentioning
confidence: 99%